A method for preparing low carbon magnesia carbon bricks
By optimizing the raw material ratio and preparation process of magnesium carbon bricks, layered forming and heat treatment methods are adopted, combined with ultrasonic detection and parameter adjustment, the problem of quality assurance of low-carbon magnesium carbon bricks is solved, and high-quality, low-carbon magnesium carbon bricks are achieved. The preparation meets the new requirements of the steel industry.
Patent Information
- Application Number
- CN202411823685.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-12-12
AI Technical Summary
In the prior art, there is a lack of monitoring of the preparation process of magnesium carbon bricks, and the quality of low-carbon magnesium carbon bricks cannot be guaranteed. Especially when reducing carbon content, it may lead to a decrease in thermal shock stability and slag permeability.
By optimizing raw material ratio and improving the preparation process, low-carbon magnesium carbon bricks are prepared by layering molding and heat treatment methods, and ultrasonic detection is used to determine whether there are cracks in the low-carbon magnesium carbon bricks. The molding parameters are adjusted according to the crack distribution method to improve the cracks. quality.
The high-quality preparation of low-carbon magnesium carbon bricks has been achieved, the cracking phenomenon is avoided, the thermal shock stability and slag permeability of magnesium carbon bricks have been improved, and the new requirements of the steel industry for refractory materials are met.
Smart Images

Figure CN119263781B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of low-carbon magnesia-carbon bricks, and in particular to a method for preparing low-carbon magnesia-carbon bricks. Background Art
[0002] As an important refractory material, magnesia carbon bricks are widely used in the lining of converters, AC arc furnaces, DC arc furnaces and slag lines of ladles due to their excellent properties such as high temperature resistance, strong slag resistance, high thermal shock resistance and low high temperature creep. However, with the advancement of smelting technology and the development of the steel industry, the requirements for refractory materials are getting higher and higher. Traditional magnesia carbon bricks have gradually exposed some shortcomings in long-term application practice, such as high thermal conductivity leading to large heat loss, carbon increase problems when smelting quality steel or ultra-low carbon steel, and consumption of a large amount of graphite resources.
[0003] In order to solve these problems, the development of low-carbon magnesia carbon bricks with low carbon content and excellent performance has become the focus of the industry. The preparation of low-carbon magnesia carbon bricks needs to overcome the problems of thermal shock stability and decreased slag permeability caused by simply reducing the carbon content. Therefore, it is particularly important to study a preparation method that can not only reduce the carbon content but also maintain or improve the performance of magnesia carbon bricks. Against this background, a preparation method for low-carbon magnesia carbon bricks came into being. This method successfully prepared low-carbon, high-performance magnesia carbon bricks by optimizing the raw material ratio and improving the preparation process, meeting the new requirements of the steel industry for refractory materials.
[0004] China Patent Publication No.: CN102329136B discloses a method for preparing a magnesia carbon brick, specifically, a method for preparing a magnesia carbon brick that solidifies at room temperature, and belongs to the technical field of refractory materials. The preparation process is: taking magnesia sand, carbon, phenolic resin binder and light-burned dolomite powder to mix to obtain a mixed mud; if an inclined countercurrent mixer is used for mixing, the pre-mixing process can be omitted, and the required materials can be directly put into it for mixing to obtain a mixed mud. The obtained mixed mud is placed in a press mold for pressure molding to obtain a formed magnesia carbon brick; the formed magnesia carbon brick is stored at room temperature for 2-4 days to obtain a magnesia carbon brick. Due to the reduction of the baking process, the magnesia carbon brick can save the energy required for baking, which is 80-120 kg / ton in terms of standard coal. The obtained magnesia carbon brick has a high calcium oxide content, a certain high-temperature creep property, and better anti-stripping property than ordinary magnesia carbon bricks. If used as a furnace lining material for smelting stainless steel, it can extend the service life and purify molten steel.
[0005] It can be seen that the preparation method of the magnesia carbon brick has the following problems: the method omits the pre-mixing process and the finished magnesia carbon brick can be obtained by storing it at room temperature for 2-4 days, but the method lacks monitoring of the process of preparing the magnesia carbon brick and cannot guarantee the quality of the final magnesia carbon brick. Summary of the invention
[0006] To this end, the present invention provides a method for preparing low-carbon magnesia carbon bricks, so as to overcome the problem in the prior art that the process of preparing magnesia carbon bricks lacks monitoring and the quality of the finally prepared low-carbon magnesia carbon bricks cannot be guaranteed.
[0007] To achieve the above object, the present invention provides a method for preparing a low-carbon magnesia-carbon brick, comprising:
[0008] Step S1, adding magnesia, graphite, carbon black, antioxidant and binder into a mixer according to a preset ratio, stirring evenly and kneading to obtain a slurry;
[0009] Step S2, adding the clay material into a vacuum high pressure forming machine for layered forming to obtain a low carbon magnesia carbon brick body;
[0010] Step S3, heat treating the low carbon magnesia carbon brick body to obtain a low carbon magnesia carbon brick;
[0011] Step S4, performing ultrasonic testing on the low carbon magnesium carbon bricks, determining whether the low carbon magnesium carbon bricks have delamination based on the peak value of the reflected wave of the ultrasonic testing results, dividing the low carbon magnesium carbon bricks into regions according to the conditions for the existence of delamination of the low carbon magnesium carbon bricks, calculating the delamination variance based on the number of first delaminations in a single sub-region, and determining the delamination distribution mode based on the delamination variance, so as to determine the parameters for adjusting the high pressure forming process of the low carbon magnesium carbon brick body or adjusting the parameters of the mixing process based on the delamination distribution mode.
[0012] Furthermore, in step S2, the layered forming process of the low carbon magnesia carbon brick body includes:
[0013] The mud material is spread over the first layer space of the mold, and then vibrated and pressurized to obtain the first layer of low-carbon magnesia-carbon brick body;
[0014] Dividing the first layer of low carbon magnesia carbon brick blank into a plurality of sub-areas based on the upper surface of the first layer of low carbon magnesia carbon brick blank, drilling holes in the first layer of low carbon magnesia carbon brick blank based on a preset hole arrangement, and removing part of the pressure and maintaining it for a preset time;
[0015] A layer of binder is coated on the upper surface of the first layer of low carbon magnesia carbon brick blank, the mud material is spread over the second layer space of the mold, and it is vibrated and pressurized to obtain a second layer of low carbon magnesia carbon brick blank, and the sub-regions of the second layer of low carbon magnesia carbon brick blank are divided according to the sub-regions of the first layer of low carbon magnesia carbon brick blank. The above operation is repeated to obtain a third layer of low carbon magnesia carbon brick blank until the low carbon magnesia carbon brick blank is obtained.
[0016] Furthermore, in the step S1, the order of adding the magnesia, the graphite, the carbon black, the antioxidant and the binder is magnesia-graphite-binder-nano carbon black-antioxidant.
[0017] Furthermore, in the step S3, heat treating the low carbon magnesia carbon brick body comprises baking the low carbon magnesia carbon brick body in a high temperature environment for 24 hours, wherein the temperature range of the high temperature environment is 150-200°C.
[0018] Further, in step S4, the process of ultrasonically testing the low carbon magnesia carbon brick to determine whether the low carbon magnesia carbon brick has spalling includes:
[0019] Ultrasonic testing of low carbon magnesia carbon bricks based on their sub-areas;
[0020] Acquire a reflection signal waveform diagram of ultrasonic testing based on a single sub-area, and compare it with a standard reflection signal waveform diagram;
[0021] The presence of spalling is determined based on the comparison result that the peak value of the reflected wave is smaller than the preset peak value.
[0022] Furthermore, in step S4, the process of determining the spalling distribution mode based on ultrasonic detection includes:
[0023] The spalling variance of low carbon MgO-C bricks is calculated based on the number of first spallings in a single sub-region;
[0024] comparing the spalling variance with a preset variance;
[0025] Determining that the distribution mode of spalling is uniform distribution based on a comparison result that the spalling variance is less than or equal to the preset variance;
[0026] Determining that the distribution of spalling is non-uniform distribution based on a comparison result that the spalling variance is greater than the preset variance;
[0027] The first spalling number is the number of peaks whose reflected wave peak value is smaller than the preset peak value.
[0028] Further, the process of adjusting the number of holes based on the uniform distribution condition includes:
[0029] Counting the number of second layer cracks of each layer of low-carbon magnesia-carbon brick blank, and comparing the number of second layer cracks with a preset number;
[0030] adjusting the number of holes based on a comparison result that the second number of spallings is greater than the preset number;
[0031] Based on a first difference percentage between the second spalling number and the preset number, several adjustment methods are set for the hole number, and the increase in the hole number by each adjustment method is positively correlated with the first difference percentage.
[0032] Further, the process of adjusting the vibration frequency based on the uniform distribution condition includes:
[0033] adjusting the vibration frequency based on a comparison result that the second number of spallings is less than or equal to the preset number;
[0034] Based on a second difference percentage between the preset number and the second spalling number, several adjustment methods are set for the vibration frequency, and the increase of the vibration frequency by each adjustment method is positively correlated with the second difference percentage.
[0035] Further, the process of adjusting the stirring rate based on the non-uniform distribution condition includes:
[0036] Determine a difference between a maximum number of spallings and a minimum number of spallings based on the first number of spallings, and compare the difference with a preset difference;
[0037] Determining to adjust the stirring rate based on the comparison result that the difference is greater than the preset difference;
[0038] Based on a first difference between the difference and the preset difference, several adjustment methods are set for the stirring rate, and the increase of the stirring rate by each adjustment method is positively correlated with the first difference.
[0039] Further, the process of adjusting the stirring time based on the non-uniform distribution condition includes:
[0040] Determining the adjustment stirring time based on the comparison result that the difference is less than or equal to the preset difference;
[0041] Based on the preset difference and a second difference of the difference, several adjustment methods are set for the stirring time, and the increase of the stirring time by each adjustment method is positively correlated with the second difference.
[0042] Compared with the prior art, the beneficial effect of the present invention lies in that the present invention prepares low carbon magnesium carbon bricks by setting a layered molding method, and drills holes after the single-layer low carbon magnesium carbon brick body is formed to facilitate the discharge of gas in the low carbon magnesium carbon brick body, so as to avoid the expansion of gas in the body after the pressure is withdrawn, resulting in layer cracking in the low carbon magnesium carbon brick, and ultrasonic detection is performed on the finally formed low carbon magnesium carbon brick, and whether there is layer cracking in the low carbon magnesium carbon brick is determined according to the reflected signal waveform diagram, and the layer cracking distribution mode is determined in the case of layer cracking. Based on the uniform distribution, the number of holes or the vibration frequency is increased to allow the gas to be better discharged. The non-uniform distribution is caused by uneven mixing of raw materials. The mixing rate or mixing time is increased to improve the uniformity of the mud material to avoid layer cracking caused by uneven mud material, thereby improving the quality of the low carbon magnesium carbon brick.
[0043] Furthermore, the present invention performs ultrasonic detection on the prepared low-carbon magnesium carbon bricks to determine whether there is delamination based on the peak value of the reflected wave. When the ultrasonic wave encounters delamination, part of its energy is absorbed, and the peak value of the reflected wave will be lower than the reflected wave without delamination. The height of the peak indicates the size of the delamination. The larger the delamination gap, the lower the peak. The number of peaks lower than the preset peaks indicates the number of delaminations, thereby improving the detection accuracy of delamination and further improving the quality of the low-carbon magnesium carbon bricks.
[0044] Furthermore, the present invention increases the number of holes or increases the vibration frequency based on the uniform distribution of layer cracks, thereby increasing the gas discharge rate, and increases the mixing rate or mixing time based on the non-uniform distribution of layer cracks, thereby increasing the uniformity of the mud material, thereby further improving the quality of the low-carbon magnesia carbon bricks. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a flow chart of a method for preparing a low-carbon magnesia-carbon brick according to an embodiment of the present invention;
[0046] Figure 2 It is a structural schematic diagram of a vacuum high pressure forming machine according to an embodiment of the present invention;
[0047] Figure 3 A flow chart for determining whether a low-carbon magnesia-carbon brick has spalling according to an embodiment of the present invention;
[0048] Figure 4 A flow chart for determining a spalling distribution method according to an embodiment of the present invention;
[0049] In the figure: 1. first robotic arm; 2. brick mold; 3. second robotic arm; 4. pressure plate; 5. drilling needle; 6. vibration component; 7. box. DETAILED DESCRIPTION
[0050] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0051] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0052] It should be noted that, in the description of the present invention, terms such as "up", "down", "left", "right", "inside" and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is merely for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present invention.
[0053] In addition, it should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0054] See also Figure 1-Figure 4 As shown, Figure 1 This is a flow chart of a method for preparing a low-carbon magnesia-carbon brick according to an embodiment of the present invention; Figure 2 It is a structural schematic diagram of a vacuum high pressure forming machine according to an embodiment of the present invention; Figure 3 A flow chart for determining whether a low-carbon magnesia-carbon brick has spalling according to an embodiment of the present invention; Figure 4 The present invention is a flowchart of determining a spalling distribution method according to an embodiment of the present invention.
[0055] The embodiment of the present invention provides a method for preparing a low-carbon magnesia-carbon brick, comprising:
[0056] Step S1, adding magnesia, graphite, carbon black, antioxidant and binder into a mixer according to a preset ratio, stirring evenly and kneading to obtain a slurry;
[0057] Step S2, adding the clay material into a vacuum high pressure forming machine for layered forming to obtain a low carbon magnesia carbon brick body;
[0058] Step S3, heat treating the low carbon magnesia carbon brick body to obtain a low carbon magnesia carbon brick;
[0059] Step S4, ultrasonically detecting the low carbon magnesium carbon brick to determine whether the low carbon magnesium carbon brick has layer cracks and the distribution of the layer cracks, and adjusting the parameters of the high pressure forming process of the low carbon magnesium carbon brick body or adjusting the parameters of the mixing process based on the distribution of the layer cracks.
[0060] Specifically, the magnesia sand is selected from fused magnesia sand or sintered magnesia sand containing 95%-99% magnesium oxide. These magnesia sands are characterized by high purity, large crystal grains and dense structure, which are beneficial to improving the slag erosion resistance and thermal shock stability of magnesia carbon bricks; the graphite is selected from natural flaky graphite, which is used to improve the electrical conductivity and thermal conductivity of magnesia carbon bricks and improve the spalling resistance of magnesia carbon bricks; the carbon black is selected from nano carbon black with a size range of 10nm-80nm, which can further reduce the elastic modulus and improve the spalling resistance; the antioxidant is selected from a combination of one or more of metal aluminum, silicon, B4C, Al-Mg to reduce the degree of oxidation of carbon at high temperature and improve the antioxidant properties of magnesia carbon bricks; the binder is selected from phenolic resin, graphene or lithium carbonate to firmly combine the raw materials together to form a stable structure.
[0061] Specifically, the ratio of each raw material is magnesia: graphite: carbon black: antioxidant: binder = 85:3:2:5:5.
[0062] Specifically, the order of adding the raw materials into the mixer is magnesia-graphite-binder-nano carbon black-antioxidant. Graphite has a light density and tends to float on the surface of the mixture during stirring, resulting in reduced plasticity and formability of the mud, thus affecting the quality of low-carbon magnesia-carbon bricks.
[0063] Specifically, the pressurization method in the layered forming process of the vacuum high-pressure forming machine is light first and then heavy, and multiple pressurizations are performed to control the density uniformity of the green body, thereby improving the quality of low-carbon magnesia carbon bricks.
[0064] Specifically, vacuum high pressure forming machines include:
[0065] Box 7;
[0066] A first mechanical arm 1, used to control a pressure plate 4;
[0067] A low carbon magnesium brick mold 2, used to shape the low carbon magnesium carbon brick;
[0068] A second mechanical arm 3, used to control the drilling needle 5;
[0069] A pressure plate 4, connected to the first mechanical arm 1, for applying pressure to the mud;
[0070] A drilling needle 5, connected to the second mechanical arm 3, is used to drill holes in the low-carbon magnesia-carbon brick body;
[0071] The vibration component 6 is connected to the low-carbon magnesium carbon brick mold 2 and is used to vibrate the mud to discharge gas.
[0072] Specifically, the heat treatment method for the low carbon magnesia carbon brick is: baking the low carbon magnesia carbon brick body at 150-200°C for 24 hours.
[0073] Specifically, the ultrasonic testing instrument includes an ultrasonic flaw detector. The specific model and parameters are not limited, and non-destructive flaw detection can be performed.
[0074] Specifically, in step S2, the layered forming process of the low carbon magnesia carbon brick body includes:
[0075] The mud material is spread over the first layer space of the mold, and then vibrated and pressurized to obtain the first layer of low-carbon magnesia-carbon brick body;
[0076] Dividing the first layer of low carbon magnesia carbon brick blank into a plurality of sub-areas based on the upper surface of the first layer of low carbon magnesia carbon brick blank, drilling holes in the first layer of low carbon magnesia carbon brick blank based on a preset hole arrangement, and removing part of the pressure and maintaining it for a preset time;
[0077] A layer of binder is coated on the upper surface of the first layer of low carbon magnesia carbon brick blank, the mud material is spread over the second layer space of the mold, and it is vibrated and pressurized to obtain a second layer of low carbon magnesia carbon brick blank, and the sub-regions of the second layer of low carbon magnesia carbon brick blank are divided according to the sub-regions of the first layer of low carbon magnesia carbon brick blank. The above operation is repeated to obtain a third layer of low carbon magnesia carbon brick blank until the low carbon magnesia carbon brick blank is obtained.
[0078] Specifically, the number of layers of low carbon magnesium carbon brick blanks is determined according to the height of the low carbon magnesium carbon bricks. The height of the last layer of low carbon magnesium carbon brick blanks is the lowest and no holes are drilled to ensure the compaction density of the low carbon magnesium carbon bricks. The number of sub-areas of the low carbon magnesium carbon bricks is not specifically limited, and ultrasonic testing of each sub-area can cover the entire low carbon magnesium carbon brick.
[0079] Specifically, the holes of low-carbon magnesia-carbon bricks are evenly distributed in a single sub-area. The holes are cylindrical and penetrate the entire green body layer. The mud fills the green body during the pressing process of the next layer of green body.
[0080] Specifically, in step S4, the process of ultrasonically testing the low carbon magnesia carbon brick to determine whether the low carbon magnesia carbon brick has spalling includes:
[0081] Ultrasonic testing of low carbon magnesia carbon bricks based on their sub-areas;
[0082] Acquire a reflection signal waveform diagram of ultrasonic testing based on a single sub-area, and compare it with a standard reflection signal waveform diagram;
[0083] Determining the presence of spalling based on a comparison result that the reflected wave peak value is less than a preset peak value;
[0084] Based on the comparison result that the reflected wave peak value is greater than or equal to the preset peak value, it is determined that no spalling exists.
[0085] Specifically, the standard reflection signal waveform diagram is a reflection waveform diagram of a low-carbon magnesium carbon brick without delamination using the same ultrasonic signal for flaw detection.
[0086] Specifically, the preset peak value is determined according to the reflection waveform diagram of the ultrasonic signal.
[0087] Specifically, in step S4, the process of determining the spalling distribution mode based on ultrasonic detection includes:
[0088] The spalling variance of low carbon MgO-C bricks is calculated based on the number of first spallings in a single sub-region;
[0089] comparing the spalling variance with a preset variance;
[0090] Determining that the distribution mode of spalling is uniform distribution based on a comparison result that the spalling variance is less than or equal to the preset variance;
[0091] Determining that the distribution of spalling is non-uniform distribution based on a comparison result that the spalling variance is greater than the preset variance;
[0092] The number of first spallings in a single sub-region is the number of peaks whose peak value of the reflected wave is smaller than the preset peak value.
[0093] Specifically, the first number of spallings is the number of spallings corresponding to a single sub-region in the vertical direction.
[0094] Specifically, the value range of the preset variance is set to [0.1, 0.5], and 0.2 is preferred in the embodiment of the present invention.
[0095] Specifically, based on the uniform distribution condition, the number of second layer cracks of each layer of low-carbon magnesia-carbon brick blank is counted;
[0096] comparing the second spalling quantity with a preset quantity;
[0097] adjusting the number of holes based on a comparison result that the second number of spallings is greater than the preset number;
[0098] The vibration frequency is adjusted based on a comparison result that the second spalling number is less than or equal to the preset number.
[0099] Specifically, the second number of spallings is the number of spallings in the horizontal direction of a single layer of low-carbon magnesium carbon bricks, and the value range of the preset number is set to [3, 7], and 5 is preferred in the embodiment of the present invention.
[0100] Specifically, based on a first difference percentage between the second spalling number and the preset number, several adjustment methods are set for the hole number, and the increase in the hole number by each adjustment method is positively correlated with the first difference percentage.
[0101] It can be understood that, the larger the first difference percentage is, the greater the increase in the number of holes caused by each adjustment method is.
[0102] Specifically, based on the second difference percentage between the preset number and the second spalling number, several adjustment methods are set for the vibration frequency, and the increase of the vibration frequency by each adjustment method is positively correlated with the second difference percentage.
[0103] It can be understood that the larger the second difference percentage is, the greater the increase in the vibration frequency by each adjustment method is.
[0104] Specifically, the more holes there are, the greater the vibration frequency is, the cleaner the gas is discharged, and delamination caused by gas expansion can be avoided.
[0105] Specifically, based on the condition of the non-uniform distribution, a difference between a maximum number of spallings and a minimum number of spallings is determined based on the first number of spallings, and the difference is compared with a preset difference;
[0106] Determining to adjust the mixing rate based on the comparison result that the difference is greater than the preset difference;
[0107] The kneading time is adjusted based on the comparison result that the difference is less than or equal to the preset difference.
[0108] Specifically, the value range of the preset difference is set to [2, 5], and 3 is preferred in the embodiment of the present invention.
[0109] Specifically, based on a first difference between the difference and the preset difference, several adjustment methods are set for the stirring rate, and the increase of the stirring rate by each adjustment method is positively correlated with the first difference.
[0110] It can be understood that, the larger the first difference is, the greater the increase in the stirring rate by each adjustment method is.
[0111] Specifically, under the condition of a certain stirring time, the greater the stirring rate, the better the mixing uniformity of the raw materials.
[0112] Specifically, based on the preset difference and the second difference of the difference, several adjustment methods are set for the stirring time, and the increase of the stirring time by each adjustment method is positively correlated with the second difference.
[0113] It can be understood that, the larger the second difference is, the greater the increase in the stirring time by each adjustment method is.
[0114] Specifically, under the condition of a certain stirring rate, the longer the stirring time, the better the mixing uniformity of the raw materials.
[0115] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A method for preparing low-carbon magnesia-carbon bricks, characterized in that: include: Step S1, adding magnesia, graphite, carbon black, antioxidant and binder into a mixer according to a preset ratio, stirring evenly and kneading to obtain a slurry; Step S2, adding the clay material into a vacuum high pressure forming machine for layered forming to obtain a low carbon magnesia carbon brick body; Step S3, heat treating the low carbon magnesia carbon brick body to obtain a low carbon magnesia carbon brick; Step S4, performing ultrasonic testing on the low-carbon magnesium carbon bricks, determining whether the low-carbon magnesium carbon bricks have spalling based on the peak value of the reflected wave of the ultrasonic testing results, dividing the low-carbon magnesium carbon bricks into regions according to the conditions for the presence of spalling, calculating the spalling variance based on the number of first spallings in a single sub-region, and determining the spalling distribution mode based on the spalling variance, so as to determine the parameters for adjusting the high-pressure forming process of the low-carbon magnesium carbon brick body or adjusting the parameters of the mixing process based on the spalling distribution mode; In step S2, the layered forming process of the low carbon magnesia carbon brick body includes: The mud material is spread over the first layer space of the mold, and then vibrated and pressurized to obtain the first layer of low-carbon magnesia-carbon brick body; Dividing the first layer of low carbon magnesia carbon brick blank into a plurality of sub-areas based on the upper surface of the first layer of low carbon magnesia carbon brick blank, drilling holes in the first layer of low carbon magnesia carbon brick blank based on a preset hole arrangement, and removing part of the pressure and maintaining it for a preset time; A layer of binder is coated on the upper surface of the first layer of low carbon magnesia carbon brick blank, the mud material is spread over the second layer space of the mold, and it is vibrated and pressurized to obtain a second layer of low carbon magnesia carbon brick blank, and the sub-regions of the second layer of low carbon magnesia carbon brick blank are divided according to the sub-regions of the first layer of low carbon magnesia carbon brick blank. The operation is repeated to obtain a third layer of low carbon magnesia carbon brick blank until the low carbon magnesia carbon brick blank is obtained.
2. The method for preparing low carbon magnesia carbon bricks according to claim 1, characterized in that: In the step S1, the order of adding the magnesia, the graphite, the carbon black, the antioxidant and the binder is magnesia-graphite-binder-nano carbon black-antioxidant.
3. The method for preparing low carbon magnesia carbon bricks according to claim 1, characterized in that: In the step S3, heat treating the low carbon magnesia carbon brick body comprises baking the low carbon magnesia carbon brick body in a high temperature environment for 24 hours, wherein the temperature range of the high temperature environment is 150-200°C.
4. The method for preparing low-carbon magnesia-carbon bricks according to claim 3, characterized in that: In step S4, the process of ultrasonically testing the low carbon magnesia carbon brick to determine whether the low carbon magnesia carbon brick has spalling includes: Ultrasonic testing of low carbon magnesia carbon bricks based on their sub-areas; Acquire a reflection signal waveform diagram of ultrasonic testing based on a single sub-area, and compare it with a standard reflection signal waveform diagram; The presence of spalling is determined based on the comparison result that the peak value of the reflected wave is smaller than the preset peak value.
5. The method for preparing low carbon magnesia carbon bricks according to claim 4, characterized in that: In step S4, the process of determining the spalling distribution mode based on ultrasonic detection includes: The spalling variance of low carbon MgO-C bricks is calculated based on the number of first spallings in a single sub-region; comparing the spalling variance with a preset variance; Determining that the distribution mode of spalling is uniform distribution based on a comparison result that the spalling variance is less than or equal to the preset variance; Determining that the distribution of spalling is non-uniform distribution based on a comparison result that the spalling variance is greater than the preset variance; The first spalling number is the number of peaks whose reflected wave peak value is smaller than the preset peak value.
6. The method for preparing low-carbon magnesia-carbon bricks according to claim 5, characterized in that: The process of adjusting the number of holes based on the uniform distribution condition includes: Counting the number of second layer cracks of each layer of low-carbon magnesia-carbon brick blank, and comparing the number of second layer cracks with a preset number; adjusting the number of holes based on a comparison result that the second number of spallings is greater than the preset number; Based on a first difference percentage between the second spalling number and the preset number, several adjustment methods are set for the hole number, and the increase in the hole number by each adjustment method is positively correlated with the first difference percentage.
7. The method for preparing low-carbon magnesia-carbon bricks according to claim 5, characterized in that: The process of adjusting the vibration frequency based on the uniform distribution condition includes: Counting the number of second layer cracks of each layer of low-carbon magnesia-carbon brick blank, and comparing the number of second layer cracks with a preset number; adjusting the vibration frequency based on a comparison result that the second number of spallings is less than or equal to the preset number; Based on a second difference percentage between the preset number and the second spalling number, several adjustment methods are set for the vibration frequency, and the increase of the vibration frequency by each adjustment method is positively correlated with the second difference percentage.
8. The method for preparing low-carbon magnesia-carbon bricks according to claim 5, characterized in that: The process of adjusting the stirring rate based on the non-uniform distribution condition includes: Determine a difference between a maximum number of spallings and a minimum number of spallings based on the first number of spallings, and compare the difference with a preset difference; Determining to adjust the stirring rate based on the comparison result that the difference is greater than the preset difference; Based on a first difference between the difference and the preset difference, several adjustment methods are set for the stirring rate, and the increase of the stirring rate by each adjustment method is positively correlated with the first difference.
9. The method for preparing low-carbon magnesia-carbon bricks according to claim 5, characterized in that: The process of adjusting the stirring time based on the non-uniform distribution condition includes: Determine a difference between a maximum number of spallings and a minimum number of spallings based on the first number of spallings, and compare the difference with a preset difference; Determining the adjustment stirring time based on the comparison result that the difference is less than or equal to the preset difference; Based on the preset difference and a second difference of the difference, several adjustment methods are set for the stirring time, and the increase of the stirring time by each adjustment method is positively correlated with the second difference.
Citation Information
Patent Citations
Method for preparing magnesia carbon brick
CN102329136B
Method for preparing magnesia carbon brick
CN102329136A
Converter lining structure
CN105603149A